Ward Design in Relation to Postoperative Wound Infection: Part III - Smith, G. (1974)
The wound infection rates, nasal carriage rates, and nasal colonization rates were studied in a recently built surgical unit for two years when it was first opened. Five years later a further two-year period of study was undertaken. Judging by the incidence of postoperative wound infection, as far as both Staphylococcus pyogenes and Gram-negative organisms are concerned, there is no evidence that the environment has become less safe with use over the seven-year period since opening.